1998
DOI: 10.1080/00365529850166284
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Prevalence of Primary Biliary Cirrhosis, Primary Sclerosing Cholangitis, and Autoimmune Hepatitis in a Norwegian Population

Abstract: The prevalences of PBC and AIH are of the same order of magnitude and about twice as high as that of PSC. These epidemiologic data can be used to estimate the number of liver transplantations required due to autoimmune liver diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 443 publications
(69 citation statements)
references
References 14 publications
3
65
1
Order By: Relevance
“…The prevalence of PSC in the United States is reported to be 13.6 per 100000 inhabitants[4]. Norway has the highest incidence rate at 1.31 per 100000 inhabitants and a prevalence of 8.5 per 100000[17]. The true prevalence of PSC may be higher than the aforementioned estimates both nationally and internationally because cholangiography may not be widely available in many parts of the world and patients with PSC may have normal levels of serum alkaline phosphatase (ALP)[18].…”
Section: Epidemiologymentioning
confidence: 99%
“…The prevalence of PSC in the United States is reported to be 13.6 per 100000 inhabitants[4]. Norway has the highest incidence rate at 1.31 per 100000 inhabitants and a prevalence of 8.5 per 100000[17]. The true prevalence of PSC may be higher than the aforementioned estimates both nationally and internationally because cholangiography may not be widely available in many parts of the world and patients with PSC may have normal levels of serum alkaline phosphatase (ALP)[18].…”
Section: Epidemiologymentioning
confidence: 99%
“…Among the 43 enrolled studies, 22 reported the incidence of PBC [526], while 13 were relevant for PSC [13-14, 17, 27-36], and 14 provided information about epidemiology of AIH [4, 13-14, 17, 37-46]. No studies mentioned the population incidence of IgG4 related cholangitis, presumably because it is relatively rare as a new disease entity.…”
Section: Resultsmentioning
confidence: 99%
“…84 Adult estimates vary, with the incidence and prevalence ranging from 1.7 to 1.9 per 100,000 per year and from 16.9 to 42.9 per 100,000, respectively. 8587 …”
Section: Autoimmune and Cholestatic Liver Diseasesmentioning
confidence: 99%